2014
DOI: 10.1165/rcmb.2013-0129oc
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Epigenetic Modulation of Human Rhinovirus–Induced CXCL10 Production by Cigarette Smoke

Abstract: Human rhinovirus (HRV) triggers exacerbations of asthma and chronic obstructive pulmonary disease. Cigarette smoking is the primary risk factor for the development of chronic obstructive pulmonary disease, and 25% of individuals with asthma smoke. Smokers experience both longer and more severe colds. We previously showed that cigarette smoke extract (CSE) inhibited HRV-induced expression of a range of epithelial antiviral molecules. Here, we use CXCL10 as a model antiviral gene to examine the mechanisms by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 49 publications
1
30
1
Order By: Relevance
“…To address the above issues, we performed a series of in vitro functional and transcriptomic experiments with a human airway epithelial cell line (Calu‐3) exposed to cannabis smoke, with tobacco smoke used as a positive control. To model cannabis smoke exposure, we used smoke conditioned media methods that have been validated for tobacco combustion experiments (Wirtz and Schmidt, ; Bernhard et al, ; Bauer et al, ; Hudy et al, ; Hudy and Proud, ; Hudy et al, ; Amatngalim et al, ; Jamieson et al, ). Comparison of differential gene expression patterns from our tobacco smoke conditioned media experiments in Calu‐3 cells to bronchial brushings from human tobacco smokers (Harvey et al, ; Tilley et al, ) and air‐liquid interface cultures of primary epithelial cells exposed to mainstream tobacco smoke (Mathis et al, ; Haswell et al, ; Haswell et al, ) revealed overlap, validating the relevance of our model.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above issues, we performed a series of in vitro functional and transcriptomic experiments with a human airway epithelial cell line (Calu‐3) exposed to cannabis smoke, with tobacco smoke used as a positive control. To model cannabis smoke exposure, we used smoke conditioned media methods that have been validated for tobacco combustion experiments (Wirtz and Schmidt, ; Bernhard et al, ; Bauer et al, ; Hudy et al, ; Hudy and Proud, ; Hudy et al, ; Amatngalim et al, ; Jamieson et al, ). Comparison of differential gene expression patterns from our tobacco smoke conditioned media experiments in Calu‐3 cells to bronchial brushings from human tobacco smokers (Harvey et al, ; Tilley et al, ) and air‐liquid interface cultures of primary epithelial cells exposed to mainstream tobacco smoke (Mathis et al, ; Haswell et al, ; Haswell et al, ) revealed overlap, validating the relevance of our model.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there was a trend towards higher prevalence of smokers in HRV þ asthmatics versus HRV À asthmatics in our study. Cigarette smoke has been shown to down-regulate bronchial epithelial release of antiviral proteins, for example CXCL10, in response to rhinovirus infection [25,26], via the inhibition of multiple transcriptional pathways linked to innate immune responses [27]. Wos and colleagues have previously demonstrated that HRV can be detected in the lower respiratory tract of asthmatic patients more frequently than in healthy controls, in the absence of recent asthma exacerbations or signs of common cold [7].…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of CCL3 is reported in the rectal biopsies of patients with IBD. 23 Since rhinovirus infection activates pDC through TLR7 and 8 pathways, 11 CSE may disrupt a signaling pathway of TLR7 and 8, contributing to the decrease in elevated CXCL10 after CSE exposure in UC samples. 12 We observed that the decreased CCL3 from DC derived from patients with UC was associated with increased Foxp3+ T cells from patients with UC after CSE exposure, suggesting that an effect of CSE on DC from patients with UC was to increase DC ability to generate Foxp3+ T cells.…”
Section: Discussionmentioning
confidence: 99%